How we can modify the risk of breast cancer? - Zbucka, Monika; Leśniewska, Monika; Knapp, Paweł; Wołczyński, Sławomir (Menopause Review/Przegląd Menopauzalny, 2005)
The multi-step process of carcinogenesis can be delayed, arrested or reversed by natural or synthetic agents. There are several independent risk factors for breast cancer development. Estimation of a women’s risk for breast cancer development is essential to identifying women who are most likely to benefit from chemoprevention. Treatment options for women who were at risk include increased surveillance, chemoprevention and prophylactic mastectomy. In the National Surgical Adjuvant Breast and Bowel Project (NSABP) PI tamoxifen treatment 20 mg/day resulted in a 49% and 50% reduction of invasive and non-invasive breast cancer. Raloxifene is being evaluated in comparison with tamoxifen in the STAR study. The main outcome measure is breast cancer incidence and the results are expected in 2006.